O-092 The 'Pleasure&Pregnancy' eHealth programme and its effect on the sexual functioning and ongoing pregnancy rates of couples with unexplained subfertility: a randomized controlled trial. (30th June 2022) - Dreischor, F; Dancet, E; Goddijn, M; Lambalk, C; Van Wely, M; Laan, E; Custers, I
Abstract: Study question: Does offering the 'Pleasure&Pregnancy programme' rather than expectant management affect sexual desire, pleasure and satisfaction, intercourse frequency and ongoing pregnancy rates in subfertile couples? Summary answer: The 'Pleasure&Pregnancy programme' limits the decline in sexual desire and intercourse frequency but does not affect sexual pleasure and satisfaction and ongoing pregnancy rates. What is known already: Dutch guidelines advise six months of non-interactive expectant management, in couples with unexplained subfertility and Hunault-prognosis of minimally 30%, rather than immediately starting assisted reproduction. Adherence to this advice is limited as both couples and fertility clinic staff feel an urge for action. Underpowered studies indicated that face-to-face sex-counselling may increase the pregnancy rates of these couples. Interactive eHealth programmes proved as effective as face-to-face sex counselling in other patient populations. Our group developed the interactive six months Pleasure&Pregnancy web-based programme, aiming to help couples maintain or improve sexual pleasure and activity and consequently increase chances on naturally conceived pregnancies. Study design, size, duration: This multi-centre trial randomised 701 couples between six months of the Pleasure&Pregnancy programme (n = 349) or expectant management, the current standard of care (n = 353) from 2016 to 2021. The Pleasure&Pregnancy web-based programme contains eight modules combining psychosexual education with couple communication, mindfulness and sensate focus exercises and additionally enables couples to interact with professionals and peers. Sexual outcomes were assessed with a diary and reliable questionnaires at baseline, three and six months. Participants/materials, setting, methods: Heterosexual couples with unexplained subfertility and a Hunault-prognosis of minimally 30% were included after their diagnostic work-up in 41 Dutch fertility clinics. All analyses were according to intention-to-treat principles. Differences between groups in ongoing pregnancy rates (naturally conceived within six months after randomization; primary outcome) were expressed as relative risks (RR). Linear mixed models assessed time, group and interactive effects on female/male sexual desire, pleasure and satisfaction, and intercourse frequency; mean differences (MD) are provided. Main results and the role of chance: Response rates at baseline, three and six months for the diaries assessing sexual pleasure (Quality of Sexual Experience; QSE) were, respectively: 55.8%, 33.9% and 16.8%. For the International Index of Erectile Function (IIEF) and the Female Sexual Function Index (FSFI) questionnaires assessing intercourse frequency, sexual desire and satisfaction response rates were, respectively: 83.2%, 50.8% and 41.2%. The probability of a naturally conceived ongoing pregnancy within six months after randomization did not differ between the randomized groups, and was 22% (n = 78/349) in the Pleasure&Pregnancy-group and 24% (n = 83/353) in the control group (RR 0.94; 95% CI 0.67 to 1.32). Neither did the groups differ in time to pregnancy (log rank p = 0.46). Both female and male sexual pleasure and satisfaction was comparable in both groups and did not change over time. Male sexual desire (scale 2-10) remained over time in the Pleasure&Pregnancy-group but decreased in the control group (MD 0.47, 95%CI 0.28 to 0.67, p < 0.001) and a similar trend was observed in females (MD 0.16, 95%CI -0.02 to 0.33, p = 0.086). Intercourse frequency declined over time in both groups (MD over 6 months -1.05, 95% CI -1.47 to -0.62, p < 0.01), but less in the Pleasure&Pregnancy- group (MD 0.3, 95% CI 0-0.6; p = 0.05). Limitations, reasons for caution: The intended sample size of 1164 was not reached, although the inclusion period was doubled. Web-based tracking showed limited intervention adherence, indicating the need for per protocol analysis in addition to this intention-to-treat analysis. Examining user experiences with the Pleasure&Pregnancy programme would be of interest and might explain adherence rate. Wider implications of the findings: Clinics are advised to offer the Pleasure&Pregnancy or similar programme to care for the sexual health of couples with unexplained subfertility. The Pleasure&Pregnancy programme did not increase naturally conceived ongoing pregnancy rates but did help couples maintain their sexual desire and intercourse frequency, while continuing to attempt natural conception. Trial registration number: NTR5709